Constructing value in the medial prefrontal cortex - Juchems, K (2019)
Humans and other animals are remarkably adept at integrating a vast array of information into their choices. For instance, they seamlessly integrate their own internal states and goals (e.g. being thirsty or aspiring to obtain a PhD) into their actions without extensive training. How does the brain enable them to do this efficiently? In this thesis, I will investigate three key components of this behaviour: i) how humans track accumulation of resources as information about the current state of their goals, ii) how they arbitrate between two competing goals, and iii) how remembered value information is efficiently re-weighted to support pursuit of novel goals. All reported experiments employed functional magnetic resonance imaging to localize neural responses.